The Influence of Influencers, Live Streaming Features and Electronic Word of Mouth on Fashion Product Purchasing Decisions Bostanten Bag on the Tiktok Application - Nilam Cahya Ramadani; Defrizal Defrizal (International Journal of Economics, Business and Innovation Research, 2025)
This research has a purpose analyze the influence of influencers, live streaming features, as well as e-WOM to product purchasing decisions Bostanten bag fashion product in the TikTok application. In the digital era, social media, especially TikTok, has become an effective platform for marketing products, especially in the fashion sector. The influence of influencers who have large audiences, interactions through live streaming features, and reviews and recommendations from other users via e- WOM believed has a role significant role in influencing constumer purchasing decisions. This study uses a descriptive quantitative approach approach for describe how these three variables influence the decision to purchase Bostanten bags. Data collected through the questionnaire distributed for respondents who actively used the TikTok application and had purchased fashion products through the platform. These findings give i to utility marketers optimize marketing strategies on TikTok by utilizing the influence of influencers, live streaming, and user reviews to increase consumer buying interest.